(untitled) (Acta Entomologica Serbica, 2019)
Professor Dragić Tomić, DSc, retired Full Professor of the University of Belgrade - Faculty of Forestry passed away on January 20, 2019. Professor Tomić was born on May 4, 1925 in Jalovik in the Vladimirci Municipality near Šabac. He finished elementary school and high school until the sixth grade in Šabac. His education was temporarily halted during World War II when he volunteered to join the National Liberation Army, where he remained until December 1945. After demobilization, he completed his education. In 1946, he finished the VII and VIII grades of high school and in the same year enrolled in the Forestry Department of the Faculty of Agriculture and Forestry (Department of Silviculture). He graduated in 1950, achieving the highest grade in his defense of his final paper. During the third and fourth years of study, he was a volunteer demonstrator in Forest Entomology. Upon graduating, he was appointed junior teaching assistant at the Department of Forest Protection of the Faculty of Forestry in Belgrade. He was elected as a teaching assistant for the first time in 1954. After two re-elections as teaching assistant (1957 and 1960), he was promoted to lecturer in 1962. He defended his doctoral dissertation entitled "Ecology of Pine chafer (Polyphylla fullo L.) on the Deliblato Sands" in 1965, obtaining the title of Doctor of Forestry. He was elected to the position of assistant professor in the subject Forest Entomology at the Faculty of Forestry in Belgrade in 1965, associate professor in 1971, and full professor in 1977. Since the establishment of the department at the Faculty in 1966, in addition to Forest Entomology, he taught: Horticultural Entomology, Protection of Plantations on Eroded Areas, and for a short time, Wood Protection. He retired on September 30, 1990. He died at the age of 94. Professor Tomić was a true expert. He published over a hundred scientific and professional papers in domestic and foreign journals, and the results of his work are still cited by many researchers. He had excellent knowledge of the world of harmful forest insects, and especially his favorite butterflies from the group of geometer moths (Fam. Geometridae), beetles from the group of cockchafers (Fam. Melolonthidae) and bark beetles (Fam. Curculionidae, subfamily Scolytinae), which he studied throughout his working life. His doctoral dissertation, which he defended in 1965, was a detailed study of the Pine chafer, a dangerous pest on the sandy terrains of our country, of which very little was known. He also studied other groups of harmful forest insects, both in terms of their ecology and harmfulness, as well as ways to effectively control them. His studies of harmful insects of soft broadleaves are very significant. First, he exhaustively studied and published papers on certain dangerous pests of poplar and willow, such as the small poplar borer, poplar clearwing moth, broad-shouldered leaf beetles of poplar and willow, and then, together with professors S. Živojinović and K. Vasić, he published the comprehensive paper "Harmful Insects of Soft Broadleaves" in two parts. He studied harmful insects in forest nurseries throughout his professional and scientific career. In addition to the extensive study of the Pine chafer, he studied other chafer species and provided the key for the determination of cockchafer larvae in the Deliblato Sands area. He also dealt with the fauna of bark-boring beetles and published papers on the fauna of this harmful group of insects on the mountains of Zlatar, Golija, Kosmaj and Kozjak. For many years, he studied geometer moths and published significant papers on the fauna of this group of butterflies of the Deliblato Sands, Mt. Goč, and finally the detailed paper "Fauna of Geometer Moths (Lepidoptera: Geometridae) of Serbia", published by the Serbian Academy of Sciences and Arts (SASA). He also investigated the harmful insects of urban greenery and studied the bionomy and ways of controlling some little known, as well as some allochthonous, harmful insects in Serbia. Professor Tomić was an excellent professor and educator with extensive knowledge and experience that he selflessly passed on to his students, junior colleagues and fellow professionals. His lectures were always well attended, as they were interesting and amusing for students. He is remembered by his student because an exam with Professor Tomić rarely took less than an hour. He expected a lot from his students, but he also did his best to give them the requisite knowledge. Even as a full professor, at the request of his students, he gave tutorials. None of his students ever complained about his high demands. Colleague foresters from the field often came to Professor Tomić for help or advice when they could not solve problems in forest protection. Professor Tomić had limitless patience for them. He would go to the field, give advice, write reports, and typically, he never sought financial compensation for his work or effort, something that is hard to imagine nowadays: he considered it his duty. Professor Tomić will be remembered by all of us, his former students, colleagues and associates, as a good and generous man. He was quiet, calm, tolerant, patient, hardworking and just, always willing to help others. With the passing of Professor Tomić, the branch of forest protection has lost a great scientist and expert, and for the many who knew him personally, a true friend.